Introducing Tibetan Buddhism - Geoffrey Samuel (World religions series, 2012)
"Introducing Tibetan Buddhism is the ideal starting point for students wishing to undertake a comprehensive study of Tibetan religion. This lively introduction covers the whole spectrum of Tibetan religious history, from early figures and the development of the old and new schools of Buddhism to the spread and influence of Tibetan Buddhism throughout the world. Geoffrey Samuel covers the key schools and traditions, as well as Bon, and bodies of textual material, including the writings of major lamas. He explores aspects such as the path to liberation through Sutra and Tantra teachings, philosophy, ethics, ritual, and issues of gender and national identity. Illustrated throughout, the book includes a chronology, glossary, pronunciation guide, summaries, discussion questions and recommendations for further reading to aid students' understanding and revision"--